KITÂBAH ‘ARAB PEGON KHASHÂISHUHÂ WA ISHÂMÂTUHÂ FÎ TATHWÎR TA’LÎM AL-LUGHAH AL-‘ARABIYYAH BI INDÛNÎSIYYÂ - Sahal Mahfud; Halimi Zuhdy (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aims to determine the characteristics and contribution of Arab Pegon script in the development of learning Arabic language in Indonesia. The Pegon script is an Arabic sript modified to write the Javanese, Sundanese, Madurese and Indonesian language. The phonological system of the Pegon script is based on the Javanese phonological system “Hanacaraka”, so that the consonants are twenty-one, and the vowels are seven. The Pegon script has similarities and differences with Arabic script and Jawi script developed and used in Malaysia, Brunei, Singapore and Pattani Thailand. Arabic Pegon script has a real contribution in the development of learning Arabic in Indonesia. Contribution of Pegon script is found in the teaching of yellow book (Islamic literature) in traditional Islamic boarding school, traditional Islamic school, as well as in Islamic traditional boarding school-based universities in Indonesia.